(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article comprehensively analyzes modern approaches to the integration of science and education, highlighting their pivotal role in transforming the education system. It examines the historical, theoretical, and social foundations of integration, explores the STEAM model, virtual reality (VR), artificial intelligence (AI), mobile-assisted learning (MALL), robotics, research groups, and pedagogical domains in depth. Global trends, challenges, and future prospects are discussed, with a focus on innovative approaches within the context of Uzbekistan’s education system, supported by Uzbek scholarly literature. The article provides practical recommendations to enhance educational quality and contribute to socio-economic development.